2019
DOI: 10.3389/fphar.2019.00468
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Sigma-1 Receptor Relieves Cognitive and Emotional Impairments Associated to Chronic Osteoarthritis Pain

Abstract: Osteoarthritis is the most common musculoskeletal disease worldwide, often characterized by degradation of the articular cartilage, chronic joint pain and disability. Cognitive dysfunction, anxiety and depression are common comorbidities that impact the quality of life of these patients. In this study, we evaluated the involvement of sigma-1 receptor (σ1R) on the nociceptive, cognitive and emotional alterations associated with chronic osteoarthritis pain. Monosodium iodoacetate (MIA) was injected into the knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 106 publications
5
24
0
Order By: Relevance
“…E‐52862 also reduced MIA‐induced microgliosis, consistent with the effects of the σ1 receptor antagonist BD1047 attenuating spinal microgliosis in a model of bone cancer pain (Zhu et al, ) and with the high levels of σ1 receptors reported in microglia (Gekker et al, ). Interestingly, E‐52862 was effective in preventing the increased microglial density induced by MIA in supraspinal structures (Carcolé et al, ). In addition, over‐expression of mGlu 5 receptors was completely abolished by E‐52862.…”
Section: Discussionmentioning
confidence: 99%
“…E‐52862 also reduced MIA‐induced microgliosis, consistent with the effects of the σ1 receptor antagonist BD1047 attenuating spinal microgliosis in a model of bone cancer pain (Zhu et al, ) and with the high levels of σ1 receptors reported in microglia (Gekker et al, ). Interestingly, E‐52862 was effective in preventing the increased microglial density induced by MIA in supraspinal structures (Carcolé et al, ). In addition, over‐expression of mGlu 5 receptors was completely abolished by E‐52862.…”
Section: Discussionmentioning
confidence: 99%
“…In the first experiments, baseline responses for the von Frey filaments and grip strength were established. After that, osteoarthritis pain was induced, and animals were tested again on days 19,20,22,25,26,27, and 29 after MIA injection. SS-injected mice were used as controls (six animals per group).…”
Section: Methodsmentioning
confidence: 99%
“…Microglia are likewise implicated in the progression of chronic pain, and their activation in the supraspinal areas is in part responsible for the molecular neuroplasticity changes associated with chronic pain [21] as well as the emotional disorders accompanying it [3]. Thus, microglial activation has been demonstrated in the medial prefrontal cortex and the hippocampus of animals with depressive-like conducts associated with osteoarthritis or neuropathic pain [18,22] as well as in several brain regions of depressive patients suffering chronic pain [23]. Consequently, the depressive-like behaviors accompanying chronic pain diminished with the administration of microglial inhibitors [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ICSS and facial expressions of pain, it could be argued that these responses may be self-limited and thus more suitable for testing tonic rather than chronic pain. However, several reports showed that changes in weight bearing, gait alterations, grip strength deficits, and burrowing behavior during other pathological models of pain such as osteoarthritis were maintained for relatively long periods (Chandran et al, 2009;Bryden et al, 2015;Philpott et al, 2017;Carcolé et al, 2019). Therefore, the often-seen recovery of normal values for these outcomes at much earlier time-points than mechanical allodynia may be due to a peculiarity of CFA as a pain model, which does not exert long-lasting functional impairment, rather than to the intrinsic characteristics of these outcomes.…”
Section: Are These "New" Outcomes Suitable For Use In All Pain Models?mentioning
confidence: 99%